INSTRUCTIONAL LEADERSHIP PRACTICES OF HEADS OF SENIOR HIGH SCHOOLS IN GHANA - Amakyi, Michael (Advances in Social Sciences Research Journal, 2021)
A non-experimental survey was conducted to investigate the instructional leadership practices of senior high school heads in Ghana. Data were collected using a closed-ended Likert type items from a simple randomly selected sample of a defined population of school heads of senior high schools in Ghana. Data collected were analysed using rank-ordered means and independent samples test of differences of means. The study findings revealed that the school heads frequently adopt major key practices of instructional leadership. However, the school heads most frequently adopt the practice of communicating the school’s goals. The study further revealed that differences exist the frequency at which heads of high performing schools and those of non-high performing schools adopt instructional leadership dimensions of defining the school’s goals and promoting a positive school learning climate.